2021
DOI: 10.18697/ajfand.97.19480
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of seed systems for reviving smallholder agriculture: a South African perspective

Abstract: South Africa is considered a food-secure nation; however, food insecurity is still a major challenge for many poor rural households that rely on cash incomes and government grants for survival. Furthermore, these grants are not always adequate to meet households’ basic needs and fail to provide them with the food required for food and nutrition security. Some of these households rely on agriculture to supplement their food needs, and an important aspect of this agricultural production is the seed system. Small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…The respondents including both men and women aged above 40 are generally involved with the storage of seeds in their respective homes. It was observed that they feel very confident about these practices particularly for traditional varieties which are grown in their fields as compared to hybrid varieties (Moreno et al 2006;Kiruba et al 2006;Montufar and Ayala 2019;Hlatshwayo et al 2021). Further, field experiments confirm that seeds stored above ground showed lower moisture contamination and were less vulnerable to insect attacks.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The respondents including both men and women aged above 40 are generally involved with the storage of seeds in their respective homes. It was observed that they feel very confident about these practices particularly for traditional varieties which are grown in their fields as compared to hybrid varieties (Moreno et al 2006;Kiruba et al 2006;Montufar and Ayala 2019;Hlatshwayo et al 2021). Further, field experiments confirm that seeds stored above ground showed lower moisture contamination and were less vulnerable to insect attacks.…”
Section: Discussionmentioning
confidence: 95%
“…Traditional seed system refers to the role of farmers in the management of local landraces which includes seed selection, production, storage and exchanges as gifts, bartered, and purchased from nearby markets (Jensen et al 2013;Nabuuma et al 2022). It supports the socio-cultural practices and strengthens the network of marginal farming communities (Montufar and Ayala 2019) as they rely on their ancestral knowledge systems and traditional storage techniques (Hlatshwayo et al 2021). In addition, it keeps away the diffusion of ex situ seeds which disrupts the local socio-cultural values (Brush 1991(Brush , 1995.…”
Section: Introductionmentioning
confidence: 99%
“…Mpumalanga is one of the provinces heavily reliant on agriculture as it produces a wide variety of fruits, vegetables, cereals, tea, and sugar. The production of these crops plays a significant role in the economic growth and development of Limpopo province (Hlatshwayo et al [20]). It also comprises 167 existing irrigation schemes with small-scale farmers operating on these schemes [8].…”
Section: Description Of the Study Areamentioning
confidence: 99%
“…Although a plethora of scientists and organizations have provided strategies for the agricultural industry to address problems brought by climate change, most of them failed to consider these African female farmers separately and their special situations. For instance, genetically improved seeds that are resistant to pests and drought -which are mentioned most frequently in related articles -are not easily accessible to smallholders mainly made up by women due to high seed costs and competition with large farms (Hlatshwayo et al, 2021). Thus, the adaptive seed strategy struggles to solve problems faced by African female farmers thoroughly if deeper, more fundamental social and financial restraints to women are not eliminated.…”
Section: Climate Change In Africamentioning
confidence: 99%